THE EFFECT OF PRINCIPALS' MANAGEMENT STYLES ON TEACHERS' PERFORMANCE IN PRIVATE PRIMARY SCHOOLS IN OMDURMAN LOCALITY IN SUDAN - Elkhder, Elzain ElKhalefa; Onia, Saifaldin Idris (Universitas Nurul Jadid, 2021)
The aims of this study to identify the predominant management style practiced by principals in private primary schools in Omdurman locality; to analyse the relationship between management styles and teachers' performance; and to examine the effect of management style practiced by principals on teachers' performance. The study employed survey research designs using a questionnaire. 45 of teachers were selected using simple random sampling. The results indicate that the democratic management style is the predominant style practiced in private primary schools in Omdurman locality. Laissez-faire and autocratic management styles were not practiced by principals in private primary schools in Omdurman locality. The study also revealed that management styles were low and positively correlated with the teachers' performance. Management style had an effect on teachers' performance by the contribution of the democratic management style that caused 25.1% of the variance in the teachers' performance. The study recommended schools principals should be encouraged to continue on democratic management style with taking into account other management styles according to the situation.